SERO-Epidemiology Of Syphilis In Patients Attending STD Clinics Of Himachal Pradesh - Thakur T.S; Goyal A; Sharma V.K (Wolters Kluwer Medknow Publications, 1992)
One thousand one hundred and ninety three patients attending sexually transmitted disease (STD) clinics from all the 12 districts of Himachal Pradesh were screened for VDRL reactivity. Overall reactivity was found to be 21.5%. The highest prevalence was found in district Kinnaur (39.0%) followed by district Mandl (37.4%) and district Shimla (24.3%). Maximum reactivity was observed in patients belonging to the backward areas and the least in urban patients. The control group comprised 753 voluntary blood donors, the VDRL reactivity in this group was found to be 2.9%. By quantitative test the overall reactivity at a dilution of and above was 16.6% in the test group and 1.8% in the control group. This study shows that the high prevalence of seropositivity reported by earlier workers has decreased.